The cluster organization : analysing the development of cooperative relationships - Lis, Anna Maria, 1976-; Lis, Adrian, 1977- (New York : Routledge, 2021)
"Cluster organizations are becoming more and more popular, both in developing and developed countries. Considering the development of cluster policy and the related dynamic growth of cluster initiatives in the world, the lack of sufficient knowledge on the development of cooperation in cluster organizations inhibits their development and, in many cases, causes their complete disintegration. The book provides new important elements to the current system of knowledge, filling in the cognitive and research gaps in the scientific literature on problems related to cooperation in cluster organizations. The most valuable features for the reader concern the epistemological, methodological and application aspects. The new element includes a theoretical concept which refers to the trajectory of development of cooperative relationships in cluster organizations, which facilitates the understanding and explanation of mechanisms responsible for cooperation in such organizations. The concept also has great practical advantages, especially for people implementing the idea of "clustering": coordinators, facilitators and members of cluster organizations as well as politicians and public authorities, responsible for shaping and implementing cluster policy. It will be of value to researchers, academics, and students in the fields of with an interest in organizational studies, management of innovation and technology, strategic management, industrial economics, and economic geography"--
OCLC-licensed vendor bibliographic record.
Keywords: Space in economics; Interorganizational relations; Management -- Technological innovations; Strategic planning; BUSINESS & ECONOMICS / Strategic Planning; BUSINESS & ECONOMICS / Industrial Management